Pengembangan Media Pembelajaran GAULL (Game Edukasi Wordwall) Berbasis Game Based Learning Pada Materi Asam Basa: Penelitian - Azizatul Husna; Yusnidar; Isra Miharti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The wordwall educational game is a learning aid that can be accessed via electronic devices with an internet connection. This study aims to determine the process of developing GAULL learning media based on game-based learning on acid-base material for class XII SMAN 11 Muaro Jambi and to determine the validity, practicality and effectiveness of GAULL learning media theoretically and practically. In the Acid-Base material, students are required to be able to understand the concept of acids and bases, the properties of acids and bases and acid-base indicators. Game based learning (GBL) approach is a game-based learning approach, this approach combines game elements to increase student motivation and involvement in learning. In this approach, students are required to learn but by playing. This research is a type of R&D (Research and Development) development research using the Lee & Owens model. The research instruments are in the form of questionnaires and interviews. The data analysis techniques used are qualitative data analysis based on suggestions and comments and quantitative data analysis based on the average answer score and percentage. The results of this study are that the GAULL learning media based on game based learning on acid base material obtained feasibility results based on a Likert scale with a material expert score of 4.6 (very feasible), media experts of 4.53 (very feasible), teacher assessment of 4.69 (very feasible), and from student responses it has a percentage of 91.8% (very good). Based on the results of the study, it was concluded that the development of GAULL learning media based on game based learning on acid base material that was developed obtained very feasible results conceptually as a teaching medium in chemistry learning.